2021
DOI: 10.3389/fendo.2021.767152
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Physical Activity on Glycemic Variability in Patients With Diabetes: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: PurposeThe effect of physical activity on glycemic variability remains controversial. This meta-analysis aimed to assess the overall effect of physical activity treatment on glycemic variability in patients with diabetes.MethodsPubMed/MEDLINE, Embase, and Cochrane databases were searched for clinical trials that conducted in patients with type 1 diabetes mellitus and type 2 diabetes mellitus with reports of the mean amplitude of glycemic excursion (MAGE), time in range (TIR), time above range (TAR), or time be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
1
4
1
2
Order By: Relevance
“…35 However, in a meta-analysis of people living with T1D and T2D, decreased MAGE during PA was associated with higher BMI, suggesting that it is more beneficial to be active in higher BMI context. 32 In contrast, we found that participants in the LL group have a positive correlation between BMI with CV and TAR and negative between BMI and TIR. This result suggests that although people with T1D accomplish healthy PA levels, they can still be challenged to maintain glucose control, but fat mass impact over time in the glucose range needs to be measured specifically in active people with T1D.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…35 However, in a meta-analysis of people living with T1D and T2D, decreased MAGE during PA was associated with higher BMI, suggesting that it is more beneficial to be active in higher BMI context. 32 In contrast, we found that participants in the LL group have a positive correlation between BMI with CV and TAR and negative between BMI and TIR. This result suggests that although people with T1D accomplish healthy PA levels, they can still be challenged to maintain glucose control, but fat mass impact over time in the glucose range needs to be measured specifically in active people with T1D.…”
Section: Discussioncontrasting
confidence: 70%
“…This meta-analysis included only 32 physically active persons and showed PA treatment is associated with decreased MAGE and TAR, and increased TIR. 32 In our study, the glycemic variability parameters, such as time spent in different glycemic ranges, were similar between the participant groups when analysed in daytime and nighttime. The same was observed with CV, both groups presented values below 36%, possibly because they were meeting the ATTD PA recommendation.…”
Section: Discussionsupporting
confidence: 62%
“…11 Desse modo, uma meta-análise confirmou que a atividade física melhora o controle glicêmico e sugeriu que pode estar associada a uma redução da variabilidade glicêmica, principalmente naqueles pacientes com maior IMC e menor tempo de doença, uma vez que no estágio inicial do DM2 a resistência insulínica tende a ser a principal causa da hiperglicemia. 24 Em adição, outra meta-análise concluiu que a atividade física, até menos intensa, como caminhadas, pode melhorar o controle glicêmico, induzir mudanças antropométricas e promover a qualidade de vida em pacientes com DM2. 25 A atividade física é, portanto, um fator importante para controle da glicemia e melhora a mobilidade das pessoas idosas.…”
Section: Discussionunclassified
“…Respecto a los cambios de estilo de vida podemos mencionar la incorporación de la dieta meta la pérdida de peso de un 10% del peso corporal basal en los siguientes 6 meses, con el objetivo de ir perdiendo peso a un ritmo de 0,5-1 kg por semana. (Álvarez-Mon et al, 2020) Según una revisión sistemática y Metaanálisis de Zhu et al, concluyo que el ejercicio se asoció significativamente con una reducción de la variabilidad glicémica en pacientes con DMT", al igual los pacientes más beneficiados fueron aquellos que previamente tenían un IMC mayor y mayor tiempo de la enfermedad (Zhu et al, 2021).…”
Section: Discussionunclassified